Convective Radio Frequency Thermal Therapy for Treatment of Benign Prostatic Hyperplasia: Single Office Experience with 255 Patients over 4 Years. Issue 1 (January 2020) - Mooney, Ryan; Goldberg, Kenneth; Wong, Daniel; Roehrborn, Claus
Abstract: Introduction: Convective radio frequency thermal therapy with the Rezūm ® system is a relatively new treatment for benign prostatic hyperplasia with proven short-term durability. We report an update of previously published data from a single center showing durability through 4 years. Methods: A retrospective review of 255 patients who underwent the Rezūm procedure from a single surgeon was performed, including 25 patients from the Rezūm II study, from March 2014 to April 2018. Maximum urinary flow rate, I-PSS (International Prostate Symptom Score), I-PSS-QOL (quality of life), post-void residual, medication use and adverse events were monitored. Data were analyzed at baseline, and 3, 6, 12, 24, 36 and 48 months after treatment. Results: Statistically significant improvement in maximum urinary flow rate (57.2%), I-PSS (54.7%) and I-PSS-QOL (59.2%) appear to be durable through 48 months, with improvement greater than 50% at most recent followup. We report a similarly low reoperation rate compared to the most recent data from the Rezūm II study (3.1% vs 4.4%), but with higher rates of urinary tract infection (18.8% vs 3.7%) and urinary retention (15.7% vs 3.7%). Overall satisfaction with the procedure experience (93.9%) and the outcome (90.9%) was high, with 97% of men interviewed recommending the procedure to a friend. In addition, 80% of men were able to stop all medication. Conclusions: Our experience provides the largest published cohort of patients undergoing this procedure and shows durable improvements in maximum urinary flow rate, I-PSS and I-PSS-QOL through 4 years. Patients outside of the inclusion criteria of Rezūm II appear to benefit from the procedure.